Impedance Spectroscopy Study of Charge Transfer in the Bulk and Across the Interface in Networked SnO2/Ga2O3 Core–Shell Nanobelts in Ambient Air - Maciej Krawczyk; Ryszard Korbutowicz; Patrycja Suchorska-Woźniak (Sensors)
Metal oxide core–shell fibrous nanostructures are promising gas-sensitive materials for the detection of a wide variety of both reducing and oxidizing gases. In these structures, two dissimilar materials with different work functions are brought into contact to form a coaxial heterojunction. The influence of the shell material on the transportation of the electric charge carriers along these structures is still not very well understood. This is due to homo-, hetero- and metal/semiconductor junctions, which make it difficult to investigate the electric charge transfer using direct current methods. However, in order to improve the gas-sensing properties of these complex structures, it is necessary to first establish a good understanding of the electric charge transfer in ambient air. In this article, we present an impedance spectroscopy study of networked SnO2/Ga2O3 core–shell nanobelts in ambient air. Tin dioxide nanobelts were grown directly on interdigitated gold electrodes, using the thermal sublimation method, via the vapor–liquid–solid (VLS) mechanism. Two forms of a gallium oxide shell of varying thickness were prepared via halide vapor-phase epitaxy (HVPE), and the impedance spectra were measured at 189–768 °C. The bulk resistance of the core–shell nanobelts was found to be reduced due to the formation of an electron accumulation layer in the SnO2 core. At temperatures above 530 °C, the thermal reduction of SnO2 and the associated decrease in its work function caused electrons to flow from the accumulation layer into the Ga2O3 shell, which resulted in an increase in bulk resistance. The junction resistance of said core–shell nanostructures was comparable to that of SnO2 nanobelts, as both structures are likely connected through existing SnO2/SnO2 homojunctions comprising thin amorphous layers.